2002
DOI: 10.1097/00002800-200207000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Triumph and Continuing Struggle of Nurse Practitioners in New South Wales, Australia

Abstract: Finally nurse practitioners in New South Wales, Australia, are legally recognized after more than a decade of struggle. In this article the authors provide an update on the nurse practitioner movement, including the continuing conflict with the medical profession as nursing strives to achieve full implementation and acceptance of the nurse practitioner role in New South Wales. Discussion includes nurse practitioner role legislation and authorization process. The issues and concerns expressed by the medical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…This role was seen as a vehicle to enhance professional practice and recognition and allow nurses to play a more ‘advanced’ clinical role in the delivery of health care. Unfortunately, the role has been slow to develop and evolve because of a range of impediments including an inconsistent approach across Australian states, inability to access Medicare funding, issues with licensing and regulation change and continued opposition from medical groups (Appel & Malcolm 2002, Jackson & Daly 2004, Driscoll et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This role was seen as a vehicle to enhance professional practice and recognition and allow nurses to play a more ‘advanced’ clinical role in the delivery of health care. Unfortunately, the role has been slow to develop and evolve because of a range of impediments including an inconsistent approach across Australian states, inability to access Medicare funding, issues with licensing and regulation change and continued opposition from medical groups (Appel & Malcolm 2002, Jackson & Daly 2004, Driscoll et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of the awareness of the NP role by nurses, doctors, allied health and patients is perceived as a barrier to role progression and sustainability throughout the literature (Appel and Malcolm, 2002;Clarin, 2007). For example, a study by Thrasher and Purc-Stephenson (2007) found that some registered nurses found it difficult performing tasks for patients being cared for by a NP citing confusion surrounding the NP role as the cause of the disagreement.…”
Section: (14%)mentioning
confidence: 99%
“…Legislation shortfalls have been reported as hindering autonomous NP practice (Appel and Malcolm, 2002;Driscoll et al, 2005). A number of the VNPP recommendations (1999) regarding legislation changes have already been amended, however a limitation to NP practice is the lack of provider numbers and Medicare provider numbers.…”
Section: (14%)mentioning
confidence: 99%
“…The main stated concerns of the medical professionals are that NPs will set up practice in direct competition to them and that the educational preparation of the NP is inadequate and may jeopardize patient safety. On the other hand, specialist mental health nurses argue that they have been undertaking an informal NP role, unrecognized, unrewarded, and unprotected by legislation, and they wish their expertise to be formally recognized (Appel & Malcolm 2002; Pearson & Peels 2002; Sydney Morning Herald 2002). Quite clearly partnerships and support from physicians is central to the successful development of the NP role in NSW Australia.…”
Section: Credentialingmentioning
confidence: 99%